Ribulose bisphosphate carboxylase from methanol-grown Paracoccus denitrificans. - Shively, J M (1978)
Paracoccus denitrificans grows on methanol as the sole source of energy and carbon, which it assimilates aerobically via the reductive pentose phosphate cycle. This gram-negative bacterium grew rapidly on 50 mM methanol (generation time, 7 h, 30 degrees C) in excellent yield (3 g of wet-packed cells per liter of culture). Electron microscopic studies indicated that the late-log-phase cells were coccoid, having a thick envelope surrounding a layer of more diffuse electron-dense material and a relatively electron-transparent core. Ribulose bisphosphate carboxylase in the 15,000 X g supernatant of fresh cells had specific activities (micromoles of CO2 fixed per minute per milligram of protein) of 0.026, 0.049, 0.085, 0.128, and 0.034 during the lag, early, mild-, and late log, and late stationary phases, respectively. The enzyme was purified 40-fold by pelleting at 159,000 X g, salting out, sedimentation into a 0.2 to 0.8 M linear sucrose gradient, and elution from a diethylaminoethyl-Sephadex column. The enzyme was homogeneous by the criteria of electrophoresis on polyacrylamide gels polymerized from several acrylamide concentrations and sedimentation behavior. The molecular weight of the native enzyme, as measured by gel electrophoresis and gel filtration, averaged 525,000. Sodium dodecyl sulfate dissociated the enzyme into two types of subunits with molecular weights of 55,000 and 13,600. The S20,w of the enzyme was 14.0 Km values for ribulose bisphosphate and CO2 were 0.166 and 0.051 mM, respectively, and the enzyme was inhibited to the extent of 94% by 1 mM 6-phosphogluconate.